2018
DOI: 10.3382/ps/pex421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary synbiotic supplement on behavioral patterns and growth performance of broiler chickens reared under heat stress

Abstract: This study examined the effects of a dietary synbiotic supplement on the behavioral patterns and growth performance of broiler chickens exposed to heat stress (HS). Three hundred sixty 1-day-old male Ross 708 broiler chicks were distributed among 24 floor pens (15 chicks per pen); each pen was randomly assigned to one of 3 dietary treatments containing a synbiotic at 0 (control), 0.5 (0.5X) and 1.0 (1.0X) g/kg. From d 15 to 42, birds were exposed to HS at 32°C daily from 08:00 to 17:00. Five broiler chickens w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 49 publications
3
59
1
4
Order By: Relevance
“…This suggests that supplementation with this kind of synbiotic can be used as a growth promoter. Mohammed, Jacobs, Murugesan, and Cheng () have shown that a synbiotic containing fructooligosaccharides and probiotic mixture of four microbial strains ( Lactobacillus reuteri , Enterococcus faecium , Bifidobacterium animalis and Pediococcus acidilactici ), used under heat stress condition, increased body weight, BW gain and feed intake of broilers at days 7, 14 and 42 of rearing. The beneficial effect of synbiotics on the growth of broilers was also observed by Aziz Mousavi et al (), especially in the initial weeks of rearing (0–2 weeks of age).…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that supplementation with this kind of synbiotic can be used as a growth promoter. Mohammed, Jacobs, Murugesan, and Cheng () have shown that a synbiotic containing fructooligosaccharides and probiotic mixture of four microbial strains ( Lactobacillus reuteri , Enterococcus faecium , Bifidobacterium animalis and Pediococcus acidilactici ), used under heat stress condition, increased body weight, BW gain and feed intake of broilers at days 7, 14 and 42 of rearing. The beneficial effect of synbiotics on the growth of broilers was also observed by Aziz Mousavi et al (), especially in the initial weeks of rearing (0–2 weeks of age).…”
Section: Resultsmentioning
confidence: 99%
“…Heat stress can increase body metabolism, produce large amounts of free radicals, cause lipid peroxidation, damage proteins and DNA, and lead to oxidative stress, which decreases the meat quality [2][3][4]. Due to intensive, industrial feeding and global warming, the degree of heat stress on poultry is increasing, especially in the hot and humid south in summer, which seriously restricts the development of the poultry industry [5][6][7]. Therefore, it is of great significance to find feasible methods to enhance the heat resistance of the body.…”
Section: Introductionmentioning
confidence: 99%
“…As the air temperature approaches the broilers' body surface temperature, the sensible heat loss is hampered. Since birds do not have sweat glands (Mohammed et al, 2018), they become dependent on respiratory evaporation to dissipate excess body heat since this mechanism does not depend on a thermal gradient. According to Robertshaw (2006) and Attia et al (2006), breath is the most important thermoregulatory mechanism for the maintenance of homeothermy in hot environments.…”
Section: Discussionmentioning
confidence: 99%